Climate anxiety in the Philippines: Current situation, potential pathways, and ways forward - Aruta, John Jamir Benzon R; Guinto, Renzo R * (Elsevier, 2022)
The concept of climate anxiety, or the psychological distress attributed to the climate crisis, has emerged in recent years. However, there is a lack of consensus on its definition. Some scholars characterize climate anxiety similarly with the affective, physical, and behavioral symptoms of anxiety disorders [1], while others conceptualize climate anxiety as extreme worrying which includes a wide range of emotions about climate change (e.g., anger, depression, hopelessness, frustration, etc.) [2]. Although often perceived as a negative psychological response to climate change [3], [4], [5], climate anxiety can also be viewed as an adaptive psychological response to the actual threat posed by the climate crisis. Meanwhile, eco-anxiety, a related term, tends to pertain to a wider range of environmental problems such as deforestation and pollution [6]. Some argue that climate anxiety and eco-anxiety can be used interchangeably since most environmental problems are driven by and are contributing to climate change. From this point onward, we will use the term climate anxiety when referring to eco-anxiety and climate anxiety.